Transmisión de potencia por correas planas en molinos paneleros. (1988)
The inconvenient selection of a power transmission system for sugar cane mills (those which are used in raw sugar blocks production), is the source of power losses and low performance of the machine in terms of juice extraction and milling capacity. This document shows a pulley's design methodology, and the necessary parameters to be taken into account in selecting the components of a system for power transmission by using belts of the "flat type" for that purpose.